2019
DOI: 10.1007/s11239-019-01822-z
|View full text |Cite
|
Sign up to set email alerts
|

A clinical practice-based evaluation of the RIETE score in predicting occult cancer in patients with venous thromboembolism

Abstract: The association between venous thromboembolism (VTE) and occult cancer is well established. However, the benefit of cancer screening in all VTE patients remains controversial. The Registro Informatizado Enfermedad TromboEmbólica (RIETE) score is a recently proposed risk score to identify VTE patients at high risk of occult cancer. We evaluated the performance of the RIETE score in a routine clinical setting comprising patients presenting with VTE between January 1 and December 31, 2014, at Danderyd University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Following these encouraging findings, four independent studies evaluated the RIETE score in more than 10,000 patients with provoked VTE in various settings. [13][14][15]31 A random-effects meta-analysis of the performance of the dichotomized RIETE score confirms that the risk of an underlying cancer is approximately twofold higher in those with 3 points or more (in summary, RR: 2.09; 95% CI: 1.57-2.78; ►Fig. 3).…”
Section: Risk Factors For Presence Of Occult Cancer In Patients With mentioning
confidence: 87%
See 2 more Smart Citations
“…Following these encouraging findings, four independent studies evaluated the RIETE score in more than 10,000 patients with provoked VTE in various settings. [13][14][15]31 A random-effects meta-analysis of the performance of the dichotomized RIETE score confirms that the risk of an underlying cancer is approximately twofold higher in those with 3 points or more (in summary, RR: 2.09; 95% CI: 1.57-2.78; ►Fig. 3).…”
Section: Risk Factors For Presence Of Occult Cancer In Patients With mentioning
confidence: 87%
“…30 A history of cancer should also alert clinicians for cancer, which could be either new or recurrent disease. 30,31 Finally, D-dimer levels obtained at VTE diagnosis also appear to be positively correlated with the risk of occult cancer. 11,32 For example, in a retrospective study of 824 VTE patients, cancer was diagnosed four times more frequently in those with D-dimer levels >4,000 ng/mL than in those with levels <2,000 ng/mL.…”
Section: Risk Factors For Presence Of Occult Cancer In Patients With mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown no difference between cancer incidence after provoked and unprovoked VTE: one third of occult cancers in RIETE were found in patients with provoking risk factors. In a subgroup analysis of the RIETE registry, Rossel et al found a high cumulative incidence of cancer in both unprovoked and provoked VTE cases (8.5% and 4.8%, p = 0.12) [ 30 ]. Furthermore, a similar effect was observed in the Hokusai VTE trial population, with similar cancer risks between provoked and unprovoked events (2.1% vs. 1.8%) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 However, another study found that a high RIETE score was not significantly associated with cancer diagnosis, a finding ascribed to poor predictive ability in women. 15 Improved clinical tools are needed to identify patients at high-risk for occult malignancy who may benefit from more aggressive screening for cancer.…”
Section: Scoring Systems For Vte Prognosticationmentioning
confidence: 99%